IS-OWC Point-to-Multipoint System Utilizing UDWDM Technology and NGPON Architecture - Mulyono Mulyono; Rika Susanti (Universitas Medan Area, 2026)
Inter-Satellite Optical Wireless Communication (IS-OWC) has emerged as a promising solution for long-distance satellite communications due to its high bandwidth capacity, low attenuation, and immunity to electromagnetic interference. However, most previous studies have focused on point-to-point communication systems with limited scalability and transmission capacity. This study aims to develop a point-to-multipoint IS-OWC system based on Ultra Dense Wavelength Division Multiplexing (UDWDM) and the Next-Generation Passive Optical Network (NGPON) architecture to improve transmission efficiency and the performance of multi-satellite communication networks. UDWDM is employed to enhance spectral efficiency through ultra-dense channel spacing, while the NGPON architecture enables efficient signal distribution to multiple satellite nodes. The proposed system is evaluated through simulations by varying the split ratio (1:2–1:64), transmission distance (200–40,000 km), input power (0–40 dBm), and bit rate (10 and 20 Gbps). System performance is assessed using the Bit Error Rate (BER) criterion based on the ITU-T G.698.1 recommendation, where acceptable performance is defined as BER ≤ 10⁻¹². The simulation results demonstrate reliable performance across all evaluated split ratios. At a 1:2 split ratio with an input power of 20 dBm, the proposed system achieves transmission distances of up to 16,000 km at 10 Gbps and 14,000 km at 20 Gbps while maintaining the required BER threshold. Increasing the split ratio reduces the maximum transmission distance, whereas higher input power extends the transmission range. These findings indicate that the proposed architecture is a scalable and effective solution for future high-capacity inter-satellite communication networks.